Changes in taste compounds, breaking properties, and sensory attributes during dry aging of beef from Japanese black cattle. (February 2016) - Iida, Fumiko; Miyazaki, Yuki; Tsuyuki, Risako; Kato, Kenichi; Egusa, Ai; Ogoshi, Hiro; Nishimura, Toshihide
Abstract: Analysis of the quality of highly marbled beef during dry aging for 60 days after slaughter showed that the changes in some qualities differed from those of conventional meat. The tenderness of these meats did not change during aging for 50 days but then gradually increased until day 60. The juiciness of these meats, as determined by sensory evaluation, did not change during aging for 60 days, except for a decrease on day 20. The umami intensity of these meats in the sensory evaluation and the value calculated by Glu and IMP quantification were highest on day 40. This high umami intensity was induced by the synergistic effect of umami compounds such as Glu and IMP. These results for tenderness, juiciness, umami intensity, and flavor intensity suggested that the best duration of dry aging for highly marbled beef was 40 days. Highlights: The best duration of dry aging for highly marbled beef was 40 days. The umami intensity of highly marbled beef was highest on day 40. The tenderness of highly marbled beef was high even with short-term aging.